Professores que atuam junto a adolescentes em conflito com a lei: sentidos e significados construídos sobre seus alunos e sobre sua prática - Cruz, Maria Valdenice Sousa da (2008)
Considering the alarming social situation in which many adolescents have been involved, Brazilian society has been concerned with a large range of questions: since lowering the age to be held responsible for penal acts, to how to make the Statute of the Child and the Adolescent an effective tool to be used by the authorities, till the extinction of total institutions for the young population. This is the case of CASA Foundation, local where the present study was conducted. Its aim was to identify and to discuss the sense and significant attributed by teachers working at the CASA Foundation to their students and to their own pedagogical practice. The theory that oriented the research was the Social-historical approach in Psychology, and the method can be described as having a qualitative nature. The subjects were two teachers, who answered to questionnaire to precise their social, economical and cultural level and to a semi-structured interview about the focus of the study, besides telling the research how was their life story. The results pointed out the necessity and the importance of having teachers able to construct new meanings for the social-educative work, contributing to demystify the common sense idea in which they appear as a person not motivated for the professional role, not worried about the learning of their pupils, caring less for their future. The teachers that participated in this investigation presented a distinct profile: they considered themselves as profoundly involved with their job, highly motivated to do it well, and concerned with the offering of a good schooling for the adolescents in conflict with the law. They also pointed out the necessity of following these youngsters after their period of confinement, in order to promote the continuity of their education, to avoid new infracional acts and to diminish as much as possible the number of imprisonments